Architectural Heritage and Its Role in Achieving Natural Ventilation: Traditional Local Architecture as a Model for Modern Construction (Journal of Basic and Applied Sciences, 2023)
Architectural heritage encompasses ideas, beliefs, practices, and both individual and collective energies, reflecting the dialogue between humans and nature in all its dimensions. It embodies authenticity, ensures continuity, and forms the basis for modernity. The more human life is seen as an extension of the past, the more architectural heritage symbols gain significance in defining the identity of the present.This study highlights the role of traditional architecture in Libya, which is rich with distinctive elements such as inner courtyards, mashrabiyas, and skylights. These elements were designed with specific philosophies to address climatic challenges while also holding important social, religious, aesthetic, psychological, and health-related functions. The common feature among them is their ability to achieve thermal and environmental comfort, with natural ventilation being the most essential aspect. The research emphasizes how traditional local architecture serves as a model for modern construction and contributes to achieving sustainable architectural goals.
Keywords: Architectural Heritage; Traditional Architecture; Natural Ventilation; Sustainability; Thermal Comfort